2006
DOI: 10.1016/j.str.2006.09.010
|View full text |Cite
|
Sign up to set email alerts
|

An Expanded Conformation of Single-Ring GroEL-GroES Complex Encapsulates an 86 kDa Substrate

Abstract: Electron cryomicroscopy reveals an unprecedented conformation of the single-ring mutant of GroEL (SR398) bound to GroES in the presence of Mg-ATP. This conformation exhibits a considerable expansion of the folding cavity, with approximately 80% more volume than the X-ray structure of the equivalent cis cavity in the GroEL-GroES-(ADP)(7) complex. This expanded conformation can encapsulate an 86 kDa heterodimeric (alphabeta) assembly intermediate of mitochondrial branched-chain alpha-ketoacid dehydrogenase, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 46 publications
(62 reference statements)
3
58
0
Order By: Relevance
“…The usual size limit for the substrate proteins, as shown by both in vitro and in vivo studies, is around 57 kDa, although the cis cavity is reported to theoretically accommodate larger proteins, on the order of 104 kDa (10,27,35,46). Productive in vivo folding of the proteins larger than the usual size limit, such as the 86-kDa maltose binding protein fusion and 82-kDa mitochondrial aconitase, has also been reported (9,29).…”
mentioning
confidence: 99%
“…The usual size limit for the substrate proteins, as shown by both in vitro and in vivo studies, is around 57 kDa, although the cis cavity is reported to theoretically accommodate larger proteins, on the order of 104 kDa (10,27,35,46). Productive in vivo folding of the proteins larger than the usual size limit, such as the 86-kDa maltose binding protein fusion and 82-kDa mitochondrial aconitase, has also been reported (9,29).…”
mentioning
confidence: 99%
“…On the contrary, electron microscopic studies on a singlering version of GroEL, SR1, demonstrated housing of an 86-kDa mitochondrial branched-chain α-ketoacid dehydrogenase by expanding the cavity by 80 % more than that shown in crystal structure (Chen et al 2006). Notably, productive release of the large encapsulated proteins was not demonstrated in the cis cavity.…”
Section: The Trans Mechanismmentioning
confidence: 84%
“…To arrive at unbiased models, different approaches have been taken. For instance, the multi-refine program has been used in EMAN, where several initial models of different conformations or multiple models with varying amount of added noise would give rise to the same final map (Brink et al, 2004;Chen et al, 2006). Alternatively, Yan and coworkers (Yan et al, 2007) proposed the Random Model (RM) method and showed that random models can be effective starting models.…”
Section: Model-bias-free Reconstructionmentioning
confidence: 99%
“…smaller B expt ) is the way to improve the resolution or to reduce the number of particles needed to achieving a certain resolution. However, for some other specimens, one may additionally need to handle the conformational homogeneity (Chen et al, 2006) and/or symmetry preservation computationally. Our study supports the notion made previously (Borgina et al, 2004) that only a small number of high quality particle images are enough to detect secondary structure elements, but the exact number of particle images may differ from case to case as demonstrated in the current investigation.…”
Section: Relation Of Number Of Particles To Resolution In Single Partmentioning
confidence: 99%